Characterization of the biosecurity measures of poultry farms in the province of Coronel Portillo, Ucayali – Peru - Germany G., Lluvis (2019)
The objective of the study was to characterize the biosecurity measures of the poultry farms located in the province of Coronel Portillo, Ucayali - Peru. Fifty-three farms distributed in the districts of Campo Verde, Yarinacocha, Manantay, Callería and Nueva Requena were evaluated through a survey to the manager of the establishment. The data collected was verified visually and through records. Biosecurity measures were evaluated according to compliance, being 1 = met and 0 = not met. Twenty-nine farms were in a sanitary void, so the data of uniformity of the flocks and the handling of feed were not obtained. Within the seven obligatory biosecurity measures, all the farms had a disinfection program and 98.1% had a disposal system for dead birds; nevertheless, no farm complied with the seven measures, being the biggest problem the lack of human capacity building, where only 15.1% of farms complied. The complementary biosecurity measures were implemented in a variable way between the farms and between the districts.